CTAZ: a safeguard factor of antiviral response. (17th April 2019) - Strano, Sabrina; Blandino, Giovanni
Abstract : The antiviral response is a tightly regulated process that follows specific patterns of timing and duration. The type I interferon‐induced antiviral pathway is driven by JAK‐STAT signalling. This is characterized by the dimerization of the receptor upon ligand binding, inducing cytoplasmic protein–protein interactions between phosphorylated STAT1 and STAT2, dimerization and nuclear translocation, which leads to the formation of a trimeric transcriptional competent complex, followed by INF‐inducible gene expression. Aberrant activation and timing of JAK‐STAT signalling might result in autoimmune disease. This implies that the strict regulation of this signalling pathway is essential to prevent pathological consequences. In this issue of EMBO Reports, Fang et al [1] describe an alternative variant of TAZ, called cTAZ, which fine‐tunes JAK‐STAT signalling, thereby contributing to the tight control of antiviral responses. Abstract : A study in this issue reports on an alternative variant of TAZ, called cTAZ, which fine‐tunes type I interferon‐induced JAK‐STAT signalling, thereby contributing to the tight control of antiviral innate immune responses.